Lack of Cellular Inflammation in a Non-human Primate Model of Radiation Nephropathy. Issue 5 (November 2020) - Cohen, Eric P.; Farese, Ann M.; Parker, George A.; Kane, Maureen A.; MacVittie, Thomas J.
Abstract : Abstract: Inflammation is commonly cited as a mechanism of delayed effects of acute radiation exposure (DEARE). Confirmation of its presence could provide significant insight to targeted use of treatments or mitigators of DEARE. We sought to quantify the presence of cellular inflammation in kidneys of non-human primates that developed acute and chronic kidney injury after a partial body irradiation exposure. We show herein that cellular inflammation is not found as a component of either acute or chronic kidney injury. Other mechanistic pathways of injury must be sought.